2022
DOI: 10.3389/fnagi.2022.948696
|View full text |Cite
|
Sign up to set email alerts
|

Continuous theta burst stimulation over left supplementary motor area facilitates auditory-vocal integration in individuals with Parkinson’s disease

Abstract: Accumulating evidence suggests that impairment in auditory-vocal integration characterized by abnormally enhanced vocal compensations for auditory feedback perturbations contributes to hypokinetic dysarthria in Parkinson’s disease (PD). However, treatment of this abnormality remains a challenge. The present study examined whether abnormalities in auditory-motor integration for vocal pitch regulation in PD can be modulated by neuronavigated continuous theta burst stimulation (c-TBS) over the left supplementary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that patients with PD have difficulties in integrating auditory feedback with motor systems to properly regulate their vocal production, as evidenced by significantly larger vocal adjustments for and/or greater ERP P2 responses to unexpected pitch or loudness changes relative to healthy controls ( Liu et al, 2012 ; Chen et al, 2013 ; Huang et al, 2016 ; Mollaei et al, 2016 ). More importantly, recent findings have shown auditory-vocal integration in patients with PD can be modulated by SLT or non-invasive brain stimulation, as shown by normalized and reduced vocal and ERP P2 responses to pitch perturbations after LSVT ® LOUD ( Li et al, 2021 ) or cTBS over the left SMA ( Dai et al, 2022 ). Notably, patients with PD who underwent LSVT ® LOUD exhibited a significant correlation between reduced vocal compensations for pitch perturbations and improved vocal loudness during passage reading ( Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that patients with PD have difficulties in integrating auditory feedback with motor systems to properly regulate their vocal production, as evidenced by significantly larger vocal adjustments for and/or greater ERP P2 responses to unexpected pitch or loudness changes relative to healthy controls ( Liu et al, 2012 ; Chen et al, 2013 ; Huang et al, 2016 ; Mollaei et al, 2016 ). More importantly, recent findings have shown auditory-vocal integration in patients with PD can be modulated by SLT or non-invasive brain stimulation, as shown by normalized and reduced vocal and ERP P2 responses to pitch perturbations after LSVT ® LOUD ( Li et al, 2021 ) or cTBS over the left SMA ( Dai et al, 2022 ). Notably, patients with PD who underwent LSVT ® LOUD exhibited a significant correlation between reduced vocal compensations for pitch perturbations and improved vocal loudness during passage reading ( Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…After re-referencing to the average of the electrodes on each mastoid, artifact-free trials will be averaged and baseline-corrected (−200 ms to 0) to generate an overall ERP response for each condition. A total of 24 electrodes in three regions of interest (ROIs) will be selected for statistical analysis ( Dai et al, 2022 ; Lin et al, 2022 ): frontal area, including AF3, AFz, AF4, F5, F3, F1, Fz, F2, F4, and F6; fronto-central area, including FC5, FC3, FC1, FCz, FC2, FC4, and FC6; and central area, including C5, C3, C1, Cz, C2, C4, and C6. The amplitudes and latencies of the P1, N1 and P2 components will be extracted from the averaged ERPs for each ROI.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, abnormal vocal compensation for perturbed auditory feedback has been suggested to be a potential behavioral index of declined or impaired speech motor control (Ranasinghe et al, 2017 ; Li et al, 2018 , 2021 ). More recently, non-invasive brain stimulation (NIBS) such as continuous theta burst stimulation (cTBS) has been applied over specific brain regions of aging patients with PD and SCA (Dai et al, 2022 ; Lin et al, 2022 ), resulting in a normalization of their overcompensation for vocal pitch perturbations. Therefore, NIBS may be a promising strategy that not only improves aging-related decline in the neuromotor control of speech production but also provides novel treatment of motor speech disorders that occur to aging patients with neurological disorders.…”
Section: Introductionmentioning
confidence: 99%